Drosophila Insulin-Like Peptides DILP2 and DILP5 Differentially Stimulate Cell Signaling and Glycogen Phosphorylase to Regulate Longevity - Post, Stephanie; Karashchuk, Galina; Wade, John D.; Sajid, Waseem; De Meyts, Pierre; Tatar, Marc (Frontiers in Endocrinology, 2018)
IInsulin and IGF signaling (IIS) is a complex system that controls diverse processes including growth, development, metabolism, stress responses and aging. Drosophila melanogaster IIS is propagated by eight Drosophila insulin-like peptides (DILPs), homologues of both mammalian insulin and IGFs, with various spatiotemporal expression patterns and functions. DILPs 1-7 are thought to act through a single Drosophila insulin/IGF receptor, InR, but it is unclear how the DILPs thereby mediate a range of physiological phenotypes. We determined the distinct cell signaling effects of DILP2 and DILP5 stimulation upon Drosophila S2 cells. DILP2 and DILP5 induced similar transcriptional patterns, but differed in signal transduction kinetics. DILP5 induced sustained phosphorylation of Akt, while DILP2 produced acute, transient Akt phosphorylation. Accordingly, we used phosphoproteomic analysis to identify distinct patterns of non-genomic signaling induced by DILP2 and DILP5. Across all treatments and replicates, 5250 unique phosphopeptides were identified, representing 1575 proteins. Among these peptides, DILP2, but not DILP5, dephosphorylated Ser15 on glycogen phosphorylase (GlyP), and DILP2, but not DILP5, was subsequently shown to repress enzymatic GlyP activity in S2 cells. The functional consequences of this difference were evaluated in adult Drosophila dilp mutants: dilp2 null adults have elevated GlyP enzymatic activity relative to wildtype, while dilp5 mutants have reduced GlyP activity. In flies with intact insulin genes, GlyP overexpression extended lifespan in a Ser15 phosphorylation dependent manner. In dilp2 mutants, that are otherwise long-lived, longevity was repressed by expression of phosphonull GlyP that is enzymatically inactive. Overall, DILP2, unlike DILP5, signals to affect longevity in part through its control of phosphorylation to deactivate glycogen phosphorylase, a central modulator of glycogen storage and gluconeogenesis.